Investigation on characteristics of landfill leachate and feasibility study of low-temperature vacuum evaporation treatment. Issue 5 (October 2022) - Zhang, Qun; Guo, Menglei; Xie, Jiawei; Yang, Xiaoming; Chen, Chongjun
Abstract: Leachate is characterized by poor biochemical properties and complex organic matter, which is potentially harmful to the surrounding environment. Low-temperature vacuum evaporation have been intensively studied for leachate treatment, but less attention was paid to monitoring the evolution of leachate organics. In order to analyze the component characteristics (especially organic matter) of typical landfill leachate and the feasibility of low-temperature vacuum evaporation process, fluorescence Excitation Emission Matrix (EEM) measurement coupling with Parallel Factor Analysis (PARAFAC) analysis and GC-MS was used to supplement the routine monitoring in order to reveal more insights into pollutants removal during the leachate treatment. The results showed that the main organic matter of landfill leachate was humic-like organic compounds, which accounted for 75–81%. The GC-MS showed that long-chain hydrocarbons, aromatic, aldehydes and esters compounds were abundant in the raw leachates. However, the humus and protein-based organic matter could be separated in a short time through low-temperature vacuum evaporation process, and the content of protein-based organic matter in condensate could be almost 100%, thus the biochemical properties were improved. The original CC, CO, C-N, C-O-C and other groups in the raw leachate were all disappeared after the low-temperature vacuum evaporation process, which was the essential reason for the transformation of fluorophores and improvement of biochemical properties. Graphical Abstract: ga1 Highlights: Humic substance (75%−82%) were abundant in landfill leachate. DOM fractions spectra analysis during low-temperature vacuum evaporation. The low-temperature vacuum evaporation process would be one of feasible technology for leachate treatment.